Tantangan dan Peluang dalam Moderasi Beragama: Dinamika Kehidupan Beragama di Kelurahan Sedayu Jawa Timur - Fitri Madani, Annisa; Salsabila, Arini; Ghina Aisy, Shintya; Dany Rahmat, Rizafan (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
This study examines the dynamics of religious life in Sedayu District, as well as the opportunities and challenges of implementing religious moderation in everyday life. The aim of this research is to find out how religious moderation is carried out by residents of Sedayu District and what opportunities and challenges they face. The method used in this research is the research method used by researchers in this research is a qualitative approach with descriptive methods. The research method used is a qualitative method. Data collection technique. Data collection techniques in qualitative research include observation, interviews, and documentation studies. On the other hand, there are opportunities for religious moderation in Sedayu Village. The role of technology can be utilized to facilitate the religious practices of the Sedayu Village community. Technology can be used to facilitate access to religious information and facilitate religious activities. Apart from that, religious diversity can also be used as a source of strength in building social harmony in Sedayu Village. In facing the challenges and opportunities of religious moderation in Sedayu Village, there needs to be a joint commitment from all stakeholders. Challenges such as tensions between religions can be overcome through joint efforts to understand, respect, and accept religious diversity. On the other hand, these opportunities can be optimized through interfaith collaboration, inclusive religious education, and active community participation.